Trabalho e Educação: um estudo sobre o adoecimento dos docentes contratados na Educação Básica Municipal em Uberlândia-MG: 2010-2018 - Andrade, Jacqueline de (2019)
The present work consists in the accomplishment of a Masters research belonging to the Stricto Sensu Graduate Program in Education of the Federal University of Uberlândia, in the research line entitled “Work, Society and Education”. This is a study that is part of investigations on relations between work, education and illness, particularly the illness of teachers and hired teachers of basic education of the municipal network of the city of Uberlândia, from 2010 to 2018. This study was based on the dialectical historical materialism method, performing a literature review on the approached theme, with the analysis of dissertations, articles and texts of classic and current authors, as well as documentary analysis on the Federal Laws (Constitution and LDB - Lei de Diretrizes e Bases da Educação Nacional) and Municipal laws of Uberlândia (Law No. 9626 of October 22, 2007 and Law No. 11,967 of September 29, 2014) and INEP - Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira - and IBGE - Instituto Brasileiro de Geografia e Estatística - indicators and medical records provided by the Occupational Medicine Center of the Uberlândia City Hall. The hypothesis of the work is that with all changes to which the teacher is subjected, including daily pressures to perform his work, and meet the purposes of efficiency of capitalist accumulation under precarious working conditions, in particular the work of the hired teacher, the illness of these professionals is visibly felt in the school institutions. This research is justified by stating that for the creation of efficient public policies that seek to solve the problems presented in the world of work, studies that present the real data, systematically and coherently analyzed, are required. It was developed to collaborate with future research and analysis that is possible to propose improvements to education workers.